Comparison of In-Vitro Dissolution of Griseofulvin Tablet made from Nano Particles and Solid Dispersion - Karima, Nurul; Sumaiyah, Sumaiyah; Nasution, Azizah (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: To find out the comparison of dissolution results of griseofulvin tablets made from nanoparticles, solid dispersions, and conventional materials. Interventions: Different types of active ingredients in the form of nanoparticles and solid dispersions can affect the dissolution results of tablets. Main outcomes measure: The results obtained in this study are the cumulative dissolution percentage and the order kinetics of the release of active ingredients. Conclusion: There was no significant cumulative percent drug release difference (p> 0.05) between nano particles, solid dispersions, and conventional materials. Tablets containing active nanoparticles, solid dispersions, and conventional materials show a linear relationship with a correlation coefficient (R2) close to 1, shown in zero-order kinetics models.